Functions of Burkholderia virulence factors: input from proteomics and DNA microarray analyses - Vellasamy, K.M.; Mariappan, V.; Hashim, Onn Haji; Vadivelu, J. (2012)
Burkholderia spp. consists of organisms that are extremely diverse and versatile with a natural habitat in the soil. Members of this genus, which include B. pseudomallei, B. mallei, B. thailandensis and B. cepacia, are capable of causing severe, life threatening opportunistic infection in patients who are immunocompromised. The underlying virulence mechanisms of the bacteria, their interactions with the host and the host defense mechanisms may be reflected by changes of the expression of proteins of both the pathogen as well as the host. In this article, we reviewed the current knowledge on interactions of Burkholderia spp. pathogens with their host mainly from the perspective of data that was generated from recent proteomics and DNA microarray investigations.